2021
DOI: 10.3389/fpls.2021.657451
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Fungal Lectin in Arabidopsis Enhances Plant Growth and Resistance Toward Microbial Pathogens and a Plant-Parasitic Nematode

Abstract: Coprinopsis cinerea lectin 2 (CCL2) is a fucoside-binding lectin from the basidiomycete C. cinerea that is toxic to the bacterivorous nematode Caenorhabditis elegans as well as animal-parasitic and fungivorous nematodes. We expressed CCL2 in Arabidopsis to assess its protective potential toward plant-parasitic nematodes. Our results demonstrate that expression of CCL2 enhances host resistance against the cyst nematode Heterodera schachtii. Surprisingly, CCL2-expressing plants were also more resistant to fungal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The negative effect on vegetative and reproductive growth caused by the overexpression of this gene in A. thaliana was also an unexpected outcome considering that is was contrary to published data describing lectin-induced mitosis in some root apical meristem tissues (Bonner, 2009) and to lectindependent modulation of sugar metabolism and/or signaling leading to increased plant productivity (Nonomura et al, 2020;Moradi et al, 2021). On the other hand, it was in agreement with a study in which detrimental effects on plant growth and development were reported in A. thaliana plants overexpressing a lectin receptor kinase used as a sensor for extracellular nicotinamide adenine dinucleotide and with the suppressed growth observed in A. cruentus hairy roots transformed with AhN4L-2, an homolog of AhN4L-1 (Castellanos-Arévalo, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…The negative effect on vegetative and reproductive growth caused by the overexpression of this gene in A. thaliana was also an unexpected outcome considering that is was contrary to published data describing lectin-induced mitosis in some root apical meristem tissues (Bonner, 2009) and to lectindependent modulation of sugar metabolism and/or signaling leading to increased plant productivity (Nonomura et al, 2020;Moradi et al, 2021). On the other hand, it was in agreement with a study in which detrimental effects on plant growth and development were reported in A. thaliana plants overexpressing a lectin receptor kinase used as a sensor for extracellular nicotinamide adenine dinucleotide and with the suppressed growth observed in A. cruentus hairy roots transformed with AhN4L-2, an homolog of AhN4L-1 (Castellanos-Arévalo, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…G3P is one of several putative long-distance signals of SAR ( Chanda et al., 2011 ; Gao et al., 2015 ; Vlot et al., 2021 ). Notably, Moradi et al. (2021) described that a local treatment with an exogenously applied fungal, fucose-binding lectin protein induced SAR against Pst .…”
Section: Discussionmentioning
confidence: 99%
“…(2021) described that a local treatment with an exogenously applied fungal, fucose-binding lectin protein induced SAR against Pst . Concomitantly, transcripts of genes, including the G3P biosynthetic enzyme GLY1 as well as PR-1 and RESPIRATORY BURST OXIDASE HOMOLOGS D and F ( RBOHD and F ) were induced in the lectin-inoculated leaves ( Moradi et al., 2021 ). This suggests that fucose-associated signals may promote the enrichment of G3P while also boosting local ROS signals.…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes are pathogens of Arabidopsis ( Moradi et al., 2021 ), apple ( Fallahi et al., 1998 ), tomato ( Khan and Khan, 1995 ), and wheat ( Cortese et al., 2003 ), these species could move through roots and be vector of some virus, caused root damage, yield loss. The tomato Mi-1 gene confers isolate-specific resistance against root-knot nematodes ( Seah et al., 2007 ).…”
Section: Biotic Stress From Pathogenic Bacteria Fungi Viruses Nematod...mentioning
confidence: 99%